Design and Optimization of 30/40MVA, 132/33kV Power Transformer Using Responses Surface Methodology - Sani, Sabo M.; Bakare, G. A.; Mahmood, A.; Sabo, A. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Transformer is the main apparatus of the power system for both transmission and distribution of electrical energy. It is the important component of electrical engineering because of its high efficiency and helps in step up and step down the voltage, impedance matching and circuit isolation. Team of designers, engineers and building owners struggled for high performance in order to maximize the transformer efficiencies and minimized losses, weight, volume and costs. Design and selection of material to construct a transformer core is a significant process. When designing transformers, especially power transformers, incorrect sizing of active components such as core geometry, low voltage winding and high voltage winding dimensions and tank dimensions can cause additional losses in the transformer. Determining these parameters at the design stage using optimization techniques has a very significant impact on the efficiency and cost effectiveness of the transformer. The purpose of this work is to design and optimized a practical 30/40MVA, 132/33kV, three phase power transformer using Octave and Responses Surface Methodology (RSM). From the work, it was concluded that the optimization of power transformer gives more accurate results as compared to the assume values. The percentage variations of core loss and copper loss in the optimized power transformer with respect to classical value were 4.35% and 13.48%, while that of efficiency was 0.14%.The percentage variations of reactance as well as the core area with classical values were 29.22% and 14.73%. Thus, for the accurate analysis of the result, it is important to optimize the power transformer.